2017
DOI: 10.1038/srep42882
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nuclear ribonucleoprotein A1 regulates rhythmic synthesis of mouse Nfil3 protein via IRES-mediated translation

Abstract: Nuclear factor, interleukin 3, regulated (Nfil3, also known as E4 Promoter-Binding Protein 4 (E4BP4)) protein is a transcription factor that binds to DNA and generally represses target gene expression. In the circadian clock system, Nfil3 binds to a D-box element residing in the promoter of clock genes and contributes to their robust oscillation. Here, we show that the 5′-untranslated region (5′-UTR) of Nfil3 mRNA contains an internal ribosome entry site (IRES) and that IRES-mediated translation occurs in a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…The 5= UTR of mouse fmr1 (NM_008031.2) (https://www.ncbi.nlm.nih.gov/ nuccore/NM_008031.2/) (AGGAGGCGCAGCGGAGCCCTTGGCCTCAGTCAGTCAGGCGCTGGGGAGCGTTTCG GTTTCACTTCCGGTGAGGGGCCGCGCCTGAGAGGGCGGGCAGTGAAGCAAACGGACGGCGAGCGCGGGCGGT GGCAGTGACGGCGGCGCCGCTGCCGGGGGGCGTGCGGTAACGCGGCGGCGGCGGCGGCGGCGACGGCGGCT GGGCCTCAAGCGCCTGCAGCCCACCTCCCGGAGGCGGGCTCCCGGCGCGAGGACGGACGAGAAG) was amplified from cDNA using PFU polymerase (Solgent) and was confirmed by sequencing. All the PCR products were digested with SalI/XmaI restriction enzymes (Beams) and inserted into the intercistronic region of a pRF bicistronic vector that contained both RLUC and FLUC (19,20,24,30). For the pRF bicistronic vector with the promoter deleted (ΔCMV_5=UTR), the CMV promoter was removed from the pRF bicistronic vector by digestion with BglIII/NheI restriction enzymes and self-ligation.…”
Section: Methodsmentioning
confidence: 99%
“…The 5= UTR of mouse fmr1 (NM_008031.2) (https://www.ncbi.nlm.nih.gov/ nuccore/NM_008031.2/) (AGGAGGCGCAGCGGAGCCCTTGGCCTCAGTCAGTCAGGCGCTGGGGAGCGTTTCG GTTTCACTTCCGGTGAGGGGCCGCGCCTGAGAGGGCGGGCAGTGAAGCAAACGGACGGCGAGCGCGGGCGGT GGCAGTGACGGCGGCGCCGCTGCCGGGGGGCGTGCGGTAACGCGGCGGCGGCGGCGGCGGCGACGGCGGCT GGGCCTCAAGCGCCTGCAGCCCACCTCCCGGAGGCGGGCTCCCGGCGCGAGGACGGACGAGAAG) was amplified from cDNA using PFU polymerase (Solgent) and was confirmed by sequencing. All the PCR products were digested with SalI/XmaI restriction enzymes (Beams) and inserted into the intercistronic region of a pRF bicistronic vector that contained both RLUC and FLUC (19,20,24,30). For the pRF bicistronic vector with the promoter deleted (ΔCMV_5=UTR), the CMV promoter was removed from the pRF bicistronic vector by digestion with BglIII/NheI restriction enzymes and self-ligation.…”
Section: Methodsmentioning
confidence: 99%
“…Endogenous mRNA levels were detected by quantitative real-time PCR using the StepOnePlus real-time PCR system (Applied Biosystems) with FastStart Universal SYBR Green Master (Roche), as described previously (65). Specific primer pairs for mouse Dbp (NM_016974.3), mouse pre-Dbp which primers targeted for intron regions (4), mouse Per1 (NM_011065.5 mouse Per2 (NM_011066.3), mouse Rev-erbα (NM_145434.4), mouse Hlf (NM_172563.3), mouse Tef (NM_017376.3), mouse Nfil3 (NM_017373.3) (18), mouse Bmal1 (NM_007489.4), mouse Per3 (NM_001289877.1) (20), mouse Cry1 (NM_007771.3), mouse Cry2 (NM_009963.4), human hnRNP K (NM_002140.4), and human DBP (NM_001352.4) were used for real-time PCR (the primer sequences are shown in Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that clock genes are controlled by core genes such as the BMAL1-CLOCK complex, which acts as an activator (5, 6), and Cryptochrome (Cry1 and Cry2) (7, 8) along with Period (Per1, Per2, and Per3) (9-12) genes, which function as repressors. Recently, post-transcriptional regulation of clock genes by RNA-binding proteins such as hnRNP Q (13-15), PTB (16), hnRNP D (17), hnRNP A1 (18), hnRNP R (19), and hnRNP K (20) was shown to play a role in circadian rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…Solid lines represent the mean counts (log 2 ), shaded areas (blue and red) are 95% confidence intervals, and grey areas denote nighttime. Hour indicates local clock hour (time of day) been demonstrated to regulate mef2 expression and splicing in mammalian cells and also exerts post-transcriptional control over multiple biological clock genes such as vrille/Nfil3 (Kim et al, 2017). A second heterogeneous nuclear ribonucleoprotein (hnRNP) responding to all three variables, the hnrnpk gene (p = .006), also regulates splicing and interacts with biological clocks (Nolte & Staiger, 2015).…”
Section: Interaction Of Temperature the Lunar Phase And Daily Rhythmsmentioning
confidence: 99%